Contractor readiness on construction technology: a case study on SSGF industrial construction system - Khoo, Yong Siang, 1994-, author 613801 (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2018)
Project Paper (Sarjana Muda Kejuruteraan (Awam)) - Universiti Teknologi Malaysia, 2018